O-GlcNAcylation in oral squamous cell carcinoma - Tassaporn Kongkaew (2018)
© 2018 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd Background: Two post-translational mechanisms commonly demonstrated in various cancers are protein phosphorylation and glycosylation by O-linked β-N-acetylglucosamine (O-GlcNAc). However, only phosphorylation of the epidermal growth factor receptor (EGFR)/Akt pathway has been reported in oral squamous cell carcinoma (OSCC). Therefore, we aimed to determine both post-translational modifications in OSCC tissues and in oral cancer cells compared to normal tissues and oral keratinocytes and to find correlations of these modifications with histological grading. Methods: Thirty-two OSCC and ten normal formalin-fixed and paraffin-embedded sections were probed with the anti-O-GlcNAc, anti-O-GlcNAc transferase (OGT), anti-phosphorylated-EGFRtyr1173, and anti-phosphorylated-Aktser473antibodies following standard immunohistochemistry. The immunohistochemical (IHC) score was determined using the Fromowitz standard. Whole cell lysates of oral cancer cells and normal oral keratinocytes were immunoblotted with the anti-O-GlcNAc antibody. Results: The median IHC scores of O-GlcNAc or OGT between OSCC and normal tissues were not different, whereas those of phosphorylated-EGFRtyr1173and phosphorylated-Aktser473were significantly higher in OSCC than normal tissues (P <.001 and P <.01, respectively). Similarly, expression of O-GlcNAcylated proteins in oral cancer cells and normal oral keratinocytes did not differ. In the OSCC group, the median IHC scores of O-GlcNAc and OGT were significantly lower than those of phosphorylated-EGFRtyr1173and phosphorylated-Aktser473(P <.01 and P <.001, respectively). The IHC scores of O-GlcNAc or OGT were not determined to correlate with histological grading. Conclusion: Unlike other types of cancers, our findings demonstrate that the levels of O-GlcNAcylation are not significantly increased in OSCC tissues or in oral cancer cells and are not associated with the histological grading of OSCC.